(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2016)
A new thermal method for detecting burn severity or monitoring burn wound healing is presented. The thermal measurement method avoids the need for introducing any substance or radiation to monitor blood perfusion or detect the depth of burnt tissue. The method of predicting and monitoring burns was tested experimentally by implementing four different burn severities on two pigs and monitoring the burns over five days. Averaged estimated thermal resistance and blood perfusion values were used to detect burn depth from thermal measurements. A damage function was introduced to illustrate those burns which cause third degree burns. The 20 and 75-second burns were quantified as third degree burns. The laboratory measured non-perfused layers calibrates very well with the estimated burn depth from the perfusion-thermal resistance probe. This paper has demonstrated the ability of perfusion-thermal resistance probe to characterize burn severity